"Accents of an Unknown Land": Percy Bysshe Shelley's Writings in Italian. Issue 3 (4th May 2019) - Varinelli, Valentina
ABSTRACT: Shelley scholars have largely overlooked the poet's verse and prose writings in Italian—originals and (self-)translations—on the assumption that they were written solely for Teresa "Emilia" Viviani, the dedicatee of Epipsychidion (1821), and have thus reduced them to a by-product of Shelley's brief infatuation with the young girl. Such a reading does not account for the complexity of these writings, which are by no means distinct from Shelley's contemporary production, and indeed can help to elucidate his ongoing theoretical reflections on language and translation. Nor can a purely biographical approach provide a rationale for the unusualness of a poet composing in and translating himself into a foreign language. But why did Shelley actually do so? What did he intend to do with his writings in Italian? And what is their place in Shelley's canon?